2018
DOI: 10.1111/fwb.13107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and impact of differential fouling of the zebra mussel Dreissena polymorpha on different unionid bivalves

Abstract: Macrobiofouling is an important phenomenon in the aquatic environment, resulting in economic losses and environmental changes, including negative impact on hard‐shelled animals. A freshwater invasive byssate bivalve, the zebra mussel Dreissena polymorpha (Dreissenidae), strongly affects bivalves from the family Unionidae by fouling their shells. We tested potential mechanisms explaining variable fouling of different unionids (four native species: Anodonta anatina, A. cygnea, Unio pictorum, U. tumidus and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
1
14
1
Order By: Relevance
“…Natural enemies -oystercatcher (Haematopus ostralegus), white-tailed eagle (Haliaeetus albicilla), wild boar (Sus scrofa), red fox (Vulpes vulpes), musk rat (Ondatra zibethicus) and otter (Lutra lutra) (andrzejeWski et al 2012b, Wojton et al 2012, as well as fouling rates by Dreissena polymorpha on S. woodiana in relation to native species (dzierżyńska-białończyk et al 2018(dzierżyńska-białończyk et al , Urbańska et al 2018) and parasites and symbionts of the Chinese pond mussel (yUryshynets & krasUtska 2009, cichy et al 2016 have been also analysed because it allows determining interactions and conditions that affect the rapidity of its spread. Additionally, the research conducted in Poland in recent years also considered elements accumulation ability of S. woodiana (królak & zdanoWski 2001, genotoxic potential (Woźnicki et al 2004) and qualitative and quantitative characterisation of mussel protein preparation (MPP) obtained by electrophoretic separation and differential scanning calorimetry (DSC) (konieczny et al 2016, stangierski et al 2018).…”
Section: Folia Malacol 27(4): 327-335mentioning
confidence: 99%
“…Natural enemies -oystercatcher (Haematopus ostralegus), white-tailed eagle (Haliaeetus albicilla), wild boar (Sus scrofa), red fox (Vulpes vulpes), musk rat (Ondatra zibethicus) and otter (Lutra lutra) (andrzejeWski et al 2012b, Wojton et al 2012, as well as fouling rates by Dreissena polymorpha on S. woodiana in relation to native species (dzierżyńska-białończyk et al 2018(dzierżyńska-białończyk et al , Urbańska et al 2018) and parasites and symbionts of the Chinese pond mussel (yUryshynets & krasUtska 2009, cichy et al 2016 have been also analysed because it allows determining interactions and conditions that affect the rapidity of its spread. Additionally, the research conducted in Poland in recent years also considered elements accumulation ability of S. woodiana (królak & zdanoWski 2001, genotoxic potential (Woźnicki et al 2004) and qualitative and quantitative characterisation of mussel protein preparation (MPP) obtained by electrophoretic separation and differential scanning calorimetry (DSC) (konieczny et al 2016, stangierski et al 2018).…”
Section: Folia Malacol 27(4): 327-335mentioning
confidence: 99%
“…Once the first D. polymorpha attach, their individual growth gradually pulls the unionid out of the sediment and exposes its shell to further colonization, which in P. complanata is facilitated by its strongly flattened and smooth shell. Additionally, P. complanata occurs preferentially on sand or gravel, where fouling by D. polymorpha is usually higher (Burlakova et al, 2000; Dzierżyńska‐Białończyk, Jermacz, Maćkiewicz, Gajewska, & Kobak, 2018) and more detrimental than on muddy bottom (Bowers & De Szalay, 2004; Nichols & Wilcox, 1997). In most individuals in this study, the distance between the surface of the sediment and the highest part of the shell was equal to the part of the shell encrusted with D. polymorpha ; P. complanata was not able to anchor deeply in the sediments, but instead was pulled out of the sand by the growth of attached D. polymorpha .…”
Section: Discussionmentioning
confidence: 99%
“…The unprecedented formation of M. leucophaeata druses in Marapendi Lagoon enabled the formation of a new hard and tridimensional habitat, like a reef, to be colonized by species from nearby sites and possibly increase their population densities. Similarly, other bivalves known by their invasive potential, such as Limnoperna fortunei Dunker, 1857 and Dreissena polymorpha (Pallas, 1771), also may colonize soft substrata in varied densities when the preferred hard substrata are not available (Karatayev et al 2010, Correa et al 2015, Dzierzynska-Bialonczyk et al 2018. The nucleus of M. leucophaeata druses in Marapendi Lagoon seems to be always formed by hard structures, such as empty shells of native species, and the byssus of pioneer individuals are not merely glued in sand grains.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, recent field surveys conducted by the authors in Rodrigo de Freitas Lagoon revealed that M. leucophaeata is also established therein in some mangrove roots (contrary to Rizzo et al 2014), especially those deeply submerged, possibly owing to the current scarcity of other available hard surfaces without aggregates of these bivalves. At least for D. polymorpha, large agglomerates are usually avoided by young individuals when another hard structure is available (Dzierzynska-Bialonczyk et al 2018). Following this scenario, perhaps the colonization of mangrove roots is not preferential for M. leucophaeata when other hard structures (such as some artificial ones) are abundant and free of conspecifics, which is not the case in Marapendi Lagoon, with few human-made structures in the water.…”
Section: Discussionmentioning
confidence: 99%